Patch-based classification of thyroid nodules in ultrasound images using direction independent features extracted by two-threshold binary decomposition - Prochazka, Antonin; Gulati, Sumeet; Holinka, Stepan; Smutek, Daniel (Computerized medical imaging and graphics, 2019)
Ultrasound imaging of the thyroid gland is considered to be the best diagnostic choice for evaluating thyroid nodules in early stages, since it has been marked as cost-effective, non-invasive and risk-free. Computer aided diagnosis (CAD) systems can offer a second opinion to radiologists, thereby increasing the overall diagnostic accuracy of ultrasound imaging. Although current CAD systems exhibit promising results, their use in clinical practice is limited. Some of the main limitations are that the majority use direction dependent features so, they are only compatible with static images in just one plane (axial or longitudinal), requiring precise segmentation of a nodule. Our intention has been to design a CAD system which will use only direction independent features i.e., not dependent upon the orientation or inclination angle of the ultrasound probe when acquiring the image. In this study, 60 thyroid nodules (20 malignant, 40 benign) were divided into small patches of 17 × 17 pixels, which were then used to extract several direction independent features by employing Two-Threshold Binary Decomposition, a method that decomposes an image into the set of binary images. The features were then used in Random Forests (RF) and Support Vector Machine (SVM) classifiers to categorize nodules into malignant and benign classes. Classification was evaluated using group 10-fold cross-validation method. Performance on individual patches was then averaged to classify whole nodules with the following results: overall accuracy, sensitivity, specificity and area under receiver operating characteristics (ROC) curve: 95%, 95%, 95%, 0.971 for RF and; 91.6%, 95%, 90%, 0.965 for SVM respectively. The patch-based CAD system we present can provide support to radiologists in their current diagnosis of thyroid nodules, whereby it can increase the overall accuracy of ultrasound imaging.
Keywords: Support Vector Machine; interpretace obrazu počítačem; diferenciální diagnóza; Female; ultrasonografie; Image Interpretation, Computer-Assisted; ženské pohlaví; diagnóza počítačová; uzly štítné žlázy; lidé; Sensitivity and Specificity; Ultrasonography; senzitivita a specificita; Diagnosis, Differential; Male; lidé středního věku; support vector machine; Thyroid Nodule; mužské pohlaví; Diagnosis, Computer-Assisted; Middle Aged; Humans